Empréstimos com amortizaç\~oes condicionadas à renda: Cenários de financiamento de estudantes de ensino superior no Brasil - Paulo A. Meyer M. Nascimento (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Income contingent loans (ICLs) are a financial tool that optimizes the transactional efficiencies involved in the government monopoly in taxing personal income. It protects the borrowers against periods of low income, as instalments vary according to fluctuations in their incomes over the lifetime. For decades, ICLs have combined social protection with fiscal sustainability in financing higher education students in an increasing number of countries. This paper simulates alternative ICL designs for student financing in Brazil. Copula functions are applied to capture mobility patterns in the graduates' earnings distribution in the Continuous PNAD in years 2014 and 2015. Hence repayment patterns are simulated for hypothetical ICL designs. Results allow the evaluation of fiscal and distributional implications related to parameters such as interest rates and repayment rates and thresholds. This is an ex-ante evaluation of an alternative for higher education student financing in Brazil given the fiscal constraints of public budgets. The best designs, in terms of affordability for graduates and size of taxpayer's subsidies, involve ICLs with surcharges of 25% added to the initial loan amounts, interest rates at the level of government's cost of borrowing upon graduation and above initial tax threshold, and progressive repayment rates aligned with the personal income tax brackets and equivalent to half of the respective tax rates.
Keywords: H52; H81; G17; I22; I23; I28; 330; higher education; financing; Brazil; income contingent loans; student loans